Opisthorchis viverrini infection in minute intestinal fluke endemic areas of Chiang Mai Province, Thailand - Nithikathkul C. (2014)
Background: Food-born trematode infections such as opisthochiasis are major causes of morbidity in Asia. Fish-borne trematode infections are commonly found in the northern and northeastern regions of Thailand. Several species of cyprinoid freshwater fish have been reported as secondary intermediate hosts. Objectives: To determine the prevalence of infections with Opisthorchis viverrini and other intestinal parasites in Chiang Mai Province, Thailand, which is an endemic area for minute intestinal fluke infections in Northern Thailand due to environmental characteristics and the traditional consumption of raw fish. Results: Stool samples were collected from 327 subjects from Cho Lae sub-district, Ban Pao sub-district, Mae Taeng district, Luang Nuea sub-district, Doi Saket district, and Nong Yaeng sub-district San Sai district, Chiang Mai. The subject ages were between 10 and 60 years. Of these, 144 were males and 183 were females (male to female ratio 1:1.27). Conclusion: Parasites were found in 36 stool samples (11.0%). The majority of detected parasites (17 cases, 5.2 percent) were Opisthorchis viverrini. Other intestinal parasites included hook-worms, Trichuris trichiura, and minute intestinal flukes. The highest prevalence (31.2%) was found in Cho Lae sub-district, Mae Taeng district. The prevalence of infection was significantly associated with the health behaviour of the subjects. There was no significant association with sex-distribution.